Meu Deus, seu Deus: uma análise do imaginário dos fiéis e o impacto sobre o diálogo inter-religioso entre grupos de judeus, cristãos e muçulmanos na cidade de São Paulo - Lisbôa, Gabriela Timm (2020)
This master-thesis aims to discover how laypeople of Judaism, Christianism and Islam interpret God and if their understandings correspond to the official theology and the recognition of inter-religious differences of their traditions. A second objective consists of the response to the question if the monotheistic God could be a focal point between the religions and, therefore, work as a basis for the dialogue between these tradition in question. Against this background, the thesis presents an overview of the inter-religious dialogue in western history, its requirements as well as the models and approaches developed by leading authors in this field. The underlying hypothesis is that from the perspective of the believers, everyone pray to the same God and the deity might be a common denominator and a stimulus for dialogue. For this purpose, the present draws on interviews with believers of the three monotheistic religions in the city of São Paulo. The results of this research are in the third chapter indicating convergences and divergences between the interviewed that could be departure points for a constructive coexistence